Advancing small island resilience and inclusive development through a convergence strategy in Carles, Philippines. Issue 1 (4th February 2019) - Molina, Jesusa Grace
Abstract : Purpose: Various natural, socio-cultural and economic risks confront the people of Gigantes Islands in the municipality of Carles. The islands' exposure to these hazards has aggravated poverty in the locality as demonstrated in the prevalence of unsafe livelihood activities and lack of access to health facilities. The onslaught of Supertyphoon Yolanda in 2013 has led to environmental and economic destruction, which prompted UP Visayas Foundation, Inc. to implement the Rehabilitation for Island Sustainability and Empowerment Gigantes Project, a rehabilitation initiative for the islands. The Frontline program contributed in enhancing its implementation through inclusive risk profiling. The paper aims to discuss this issue. Design/methodology/approach: One of the actions done to promote small island resilience was the institutionalization of convergence strategy to consolidate post-disaster and development efforts of government and non-government organizations at different levels. The formation of Island Sustainable Development Alliance, Inc., an umbrella organization of community-based groups involved in disaster preparedness and natural resource management, has demonstrated the beauty of convergence. Findings: Good relationships, resource mobilization and shared responsibility among stakeholders became evident as a result of collaboration. Despite challenges on consolidating the barangay development councils due to varying priorities, and conflicting interests due to survival, the strategy led to significant impacts toward addressing vulnerabilities and isolation. Originality/value: To sustain the initiative, capacity-building and advocacy efforts are implemented continuously on the ground to promote ownership and inclusive development.